Methodical approach to fixture design in the milling of thin-walled mechanical components - Nguyen Thi Anh; Tran Thanh Tung (Results in Engineering)
The milling of thin-walled mechanical components presents unique challenges due to their low structural stiffness and high susceptibility to elastic deformation under machining and clamping forces. This study proposes a methodical approach to the design and validation of a specialized fixture system tailored for such thin-walled geometries, with a focus on motorcycle gearbox housings. These components often feature complex contours, irregular wall thicknesses, and functional surfaces that demand high dimensional precision. To address these requirements, the proposed fixture incorporates profile-matching jaws and pneumatic clamping to ensure uniform load distribution, reduce deflection, and prevent localized stress on delicate wall sections. The fixture design was evaluated through finite element analysis (FEA) to assess stress distribution and displacement behavior under operational loads. Experimental validation confirmed that the fixture maintained positional accuracy, suppressed vibration, and achieved consistent machining quality. The results demonstrate the effectiveness of the proposed fixture system in improving repeatability, surface finish, and structural integrity during the milling of thin-walled components, offering a viable solution for high precision, high volume production.